Community Colleges and the Access Effect Why Open Admissions Suppresses Achievement - Scherer, Juliet Lilledahl; Anson, Mirra Leigh; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Taking on the cherished principle that community colleges should be open to all students with a high school education, Scherer and Anson argue that open access policies and lenient federal financial aid laws harm students and present the case for raising the minimum requirements for community college entry.
Keywords: Science; Science; Science, general